Transformasi Dakwah Era Digital: Analisis Strategi Konten YouTube Ar Risalah TV: The Transformation of Da'wah in the Digital Age: An Analysis of Ar Risalah TV's YouTube Content Strategy - Rina Setiawati (JOURNAL OF ISLAMIC SOCIAL SCIENCE AND COMMUNICATION (JISSC) DIKSI, 2024)
This study was motivated by the transformation of Islamic da’wah from conventional spaces to digital spaces based on video platforms, with YouTube as one of the most widely used mediums. The study aims to analyze the digital da’wah strategies of the Ar Risalah TV YouTube channel through the stages of planning, implementation, and evaluation. The study employs a descriptive qualitative approach using the case study method. Data were collected through in-depth interviews, digital observation, and documentation, and were then analyzed using the interactive model developed by Miles, Huberman, and Saldaña, which includes data reduction, data presentation, and the drawing of conclusions and verification. The results of the study indicate that Ar Risalah TV’s planning is oriented toward the dissemination of Islamic teachings and the adaptation of themes to audience needs; implementation is carried out through the production of mosque study content, live streaming, and the utilization of YouTube features such as thumbnails, playlists, and Shorts; while evaluation combines analytical data with substantive da’wah indicators. This channel’s digital da’wah strategy is adaptive and values-based, capable of balancing the logic of digital platforms with the substance of Islamic da’wah